2011
DOI: 10.1002/jcop.20485
|View full text |Cite
|
Sign up to set email alerts
|

Assessing person‐centered outcomes in practice research: a latent transition profile framework

Abstract: Advances in statistics provide new methods for analyzing practice data. These advances include person-centered methods (PCMs) that identify subgroups of research participants with similar characteristics. PCMs derive from a frame of reference that is similar to the risk factor perspective in practice. In practice, the delivery of services is often contingent on identifying at-risk populations and then providing interventions to groups based on shared risk profiles. PCMs use this perspective. Moreover, PCMs pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…Fit statistics were examined for two-to five-profile solutions. Five commonly used measures were considered in choosing the appropriate solution: the Akaike Information Criterion (AIC), the Bayesian Information Criterion (BIC), Entropy, a Lo-Mendell Rubin Test (LMR), and a Bootstrap Likelihood Ratio Test (BLRT) (Lo, Mendell, & Rubin, 2001;Nylund, Asparouhov, & Muth en, 2007;Thompson, Macy, & Fraser, 2011). These methods enable the researcher to test the changes in model fit as the number of profiles (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Fit statistics were examined for two-to five-profile solutions. Five commonly used measures were considered in choosing the appropriate solution: the Akaike Information Criterion (AIC), the Bayesian Information Criterion (BIC), Entropy, a Lo-Mendell Rubin Test (LMR), and a Bootstrap Likelihood Ratio Test (BLRT) (Lo, Mendell, & Rubin, 2001;Nylund, Asparouhov, & Muth en, 2007;Thompson, Macy, & Fraser, 2011). These methods enable the researcher to test the changes in model fit as the number of profiles (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Using LPA to identify unobservable subgroups of individuals with distinct patterns of risk behavior expands on previous work (e.g., Maynard, Salas-Wright, Vaughn, & Peters, 2012; Thompson, Macy, & Fraser, 2011) in two key ways. First, the WARNS enables development of profiles from self-reported risk and needs rather than teacher reports (Thompson et al, 2011). Therefore, perspective on the patterns of risks and needs is depicted by the students themselves, rather than a third party.…”
Section: Current Studymentioning
confidence: 93%
“…Recent work by Moynihan et al (2015) demonstrated that a combination of strategies (social marketing and in-person bystander program) sustained better outcomes over a longer period of time than a solo strategy. Further studies are needed to determine how to best sustain positive gains in changing attitudes and behaviors and more advanced analytic designs, to capture the impact of prevention programs over time, such as latent growth curve modeling (Shaw & Janulis, 2016) and person-centered analysis strategies (Swartout & Swartout, 2012; A. M. Thompson, Macy, & Fraser, 2011).…”
Section: Area 2: Preventionmentioning
confidence: 99%